Analisis Wacana Kritis Model Teun A. van Dijk dalam “#DebatKeren Papua – Budiman Sudjatmiko VS Dandhy Laksono” - Prihartono, Rachmat; Suharyo, Suharyo (Wicara: Jurnal Sastra, Bahasa, dan Budaya, 2022)
AbsractThis research is a qualitative research using the critical discourse analysis approach of the Teun A. van Dijk model. The purpose of this study is to explain the critical discourse analysis of Teun A. van Dijk's model in #DebatKeren Papua - Budiman Sudjatmiko vs. Dandhy Laksono covering the structure of the discourse that is built and the ideological discourse that is conveyed. The theory of critical discourse analysis is carried out using text analysis, social cognition, and context. The results showed that there was a macro structure (thematic) on the topic of the event, entitled Nationalism and Sepatism: Questions on Papua. The superstructure (schematic) contains an opening, a battle of ideas between Budiman Sudjatmiko and Dandhy Laksono as well as statements and questions from the audience. The micro structure of the #DebatKeren Papua involves elements of semantic, syntactic, stylistic and rhetorical discourse. In general, Budiman Sudjatmiko responded to the Papua issue with an attitude as an Indonesian nation. Meanwhile, Dandhy has a tendency to support the fate of Papua.Keywords: Critical Discourse Analysis, Teun A. van Dijk, Papua, Budiman Sudjatmiko, Dandhy Laksono AbstrakPenelitian ini adalah penelitian kualitatif menggunakan pendekatan analisis wacana kritis model Teun A. van Dijk. Tujuan penelitian ini untuk menjelaskan analisis wacana kritis model Teun A. van Dijk dalam #DebatKeren Papua - Budiman Sudjatmiko vs Dandhy Laksono meliputi struktur wacana yang dibangun dan wacana ideologi yang disampaikan. Teori analisis wacana kritis ini dilakukan dengan menggunakan analisis teks, kognisi sosial, dan konteks. Hasil penelitian menunjukkan adanya struktur makro (tematik) topik acara yang bertajuk Nasionalism and Sepatism: Questions on Papua. Superstruktur (skematik) terdapat pembuka, pertarungan gagasan antara Budiman Sudjatmiko dan Dandhy Laksono serta pernyataan dan pertanyaan dari audiens. Struktur mikro pada #DebatKeren Papua ini melibatkan elemen wacana semantik, sintaksis, stilistika dan retoris. Secara umum, Budiman Sudjatmiko menanggapi masalah Papua dengan sikap sebagai bangsa Indonesia. Sedangkan Dandhy memiliki kecenderungan mendukung nasib Papua. Kata Kunci: Analisis Wacana Kritis, Teun A. van Dijk, Papua, Budiman Sudjatmiko, Dandhy Laksono